Structural Features of the Nucleosomal DNA Modulate the Functional Binding of a Transcription Factor and Productive Transcription - Vinayachandran, Vinesh; Bhargava, Purnima (Frontiers in Genetics, 2022)
A small non-histone protein of the budding yeast, Nhp6 has been reported to specifically influence transcription of a yeast gene, SNR6. The gene is essential, transcribed by the enzyme RNA polymerase III and codes for the U6snRNA required for the mRNA splicing. A translationally positioned nucleosome on the gene body enables the assembly factor TFIIIC binding by juxtaposing its otherwise widely separated binding sites, the boxes A and B. We found histone depletion results in loss of U6 snRNA production. Changing the rotational phase of the boxes and the linear distance between them with deletions in 5 bp steps, displayed a helical periodicity in transcription, which gradually reduced with incremental deletions upto 40 bp but increased upon further deletions enclosing the pseudoA boxes. Nhp6 influences the transcription in a dose-dependent manner, which is modulated by its previously reported co-operator, an upstream stretch of seven T residues centred between the TATA box and transcription start site. Nhp6 occupancy on the gene in vivo goes up at least 2 fold under the repression conditions. Nhp6 absence, T7 disruption, or shorter A-B boxes distance; all cause downstream initiation of transcription. The right +1 site is selected with correct placement of TFIIIC and then the transcription initiation factor TFIIIB. Thus, Nhp6 and T7 sequence help assembly and placement of the transcription complex at right position. Apart from the chromatin remodelers, the relative rotational orientation of the promoter elements in nucleosomal DNA, and Nhp6 regulate transcription of the SNR6 gene with precision.